A carboxy-subterminal aromatic residue in Schizophyllum commune mating pheromones controls specific recognition by Bar4 receptor - Thomas Fowler (Fungal Genetics Reports, 2010)
Most heterothallic basidiomycetes use small lipopeptide pheromones as part of mate recognition. Schizophyllum commune has scores of pheromones that must be specifically recognized by mating receptors. A correlation between a phenylalanine residue near the C-terminus of several pheromones and the ability of those pheromones to activate receptor Bar4 was recognized. We hypothesized that the phenylalanine residue would be critical for Bar4 activation and tested the hypothesis by making site-directed mutant pheromones and testing these pheromone variants in matings. The data support the hypothesis and add to our understanding of which amino acid residues within pheromones are critical for specific recognition by pheromone receptors.